2016
DOI: 10.1080/14737175.2016.1203255
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorders: management over the lifespan

Abstract: For the majority of the autism spectrum disorder (ASD) population, symptoms begin within the first years of life and associated difficulties continue throughout the lifespan. Currently, the research literature focuses more heavily on problems in childhood. However, given that adulthood accounts for the majority of life, more focus should be placed on evidence-based, lifelong treatment and management strategies for ASD. Areas covered: This paper reviews the topic of lifelong ASD management, primarily emphasizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Autism and ASDs are neurodevelopmental and lifelong disorders featuring onset of symptoms within the first 3 years of life (Brambilla et al, 2004;Matson et al, 2016). Autism and ASD are characterized by altered cortical developmental trajectory and connectivity, as reported in several studies (Bailey et al, 1998;Casanova et al, 2002;Brambilla et al, 2003;Geschwind and Levitt, 2007;Hutsler et al, 2007;Hutsler and Zhang, 2010;Calderoni et al, 2016;Crippa et al, 2016;Hutsler and Casanova, 2016).…”
Section: The Subplate and Autismmentioning
confidence: 99%
“…Autism and ASDs are neurodevelopmental and lifelong disorders featuring onset of symptoms within the first 3 years of life (Brambilla et al, 2004;Matson et al, 2016). Autism and ASD are characterized by altered cortical developmental trajectory and connectivity, as reported in several studies (Bailey et al, 1998;Casanova et al, 2002;Brambilla et al, 2003;Geschwind and Levitt, 2007;Hutsler et al, 2007;Hutsler and Zhang, 2010;Calderoni et al, 2016;Crippa et al, 2016;Hutsler and Casanova, 2016).…”
Section: The Subplate and Autismmentioning
confidence: 99%
“…Because our review was limited to studies on psychoeducational interventions, we did not include literature reviews, meta-analyses, books, or program reports (see Eligibility Criteria and Study Selection ), although several were identified in the electronic search. However, we did manually scrutinize the reference lists of literature reviews and meta-analyses (Aylott, 2000; Bishop-Fitzpatrick et al, 2013; Broadstock et al, 2007; Brugha et al, 2015; Committee on Children With Disabilities, 1998; DeJong et al, 2014; El Achkar and Spence, 2015; Gates et al, 2017; Kasari et al, 2014; Lorenc et al, 2018; Matson et al, 2011, 2016; Millar et al, 2006; Nicholas et al, 2015; Ratto and Mesibov, 2015; Reichow and Volkmar, 2010; Reichow et al, 2013; Rutter, 1996; Schreibman, 1996; Shattuck et al, 2012; Sinha et al, 2004, 2006; Sturmey, 2012; Taylor et al, 2012; Tsai, 1999; Vismara and Rogers, 2010; Volkmar et al, 1999, 2014; Walton and Ingersoll, 2013; Weiss and Harris, 2001; Wong et al, 2015), books (Sheridan and Raffield, 2008; Volkmar et al, 2014), and program reports (Young et al, 2010) in order to identify relevant studies that did not appear in the electronic search.…”
Section: Methodsmentioning
confidence: 99%
“…attendance at university/college and employment (Matson et al, 2016;Ratto & Mesibov, 2015). Specific psychosocial interventions have been developed for autistic adults targeting communication, social interaction and flexible thinking and behavior (e.g., social skills training; applied behavior analysis) (Matson et al, 1996;Odom et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In adulthood, some of the most relevant challenges that prompt interventions arise from core symptoms (i.e., repetitive/restricted behaviors; deficits in social skills) and poor adaptive functioning that may impede independent living, attendance at university/college and employment (Matson et al, 2016 ; Ratto & Mesibov, 2015 ). Specific psychosocial interventions have been developed for autistic adults targeting communication, social interaction and flexible thinking and behavior (e.g., social skills training; applied behavior analysis) (Matson et al, 1996 ; Odom et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%